IMPLEMENTA SI PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV DI SDN 04 KOTO BESAR - Wiwik Okta Susilawati; Rusdi Indra Hasibuan; Dian Angraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is a very important part in the process of building the nation's character, this education includes a process that must be carried out by all human beings, namely learning, growing and developing human potential through the Pancasila student profile included in the Merdeka Belajar curriculum, character development in Pancasila education learning can be carried out and students' good character can be improved. The type of research conducted by researchers is descriptive qualitative research. The method that researchers use in their research is to use the observation method, interview method, and documentation method, the data analysis method used is data collection using triangulation techniques, data collection, data reduction, data presentation, conclusion drawing or verification. Based on the research data, the habits that are practiced are in accordance with the six dimensions of the Pancasila student profile, namely faith, devotion to God Almighty and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity.